2010
DOI: 10.1113/jphysiol.2010.197004
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium attenuates chronic hypersensitivity and spinal cord NMDA receptor phosphorylation in a rat model of diabetic neuropathic pain

Abstract: Neuropathic pain is a common diabetic complication affecting 8-16% of diabetic patients. It is characterized by aberrant symptoms of spontaneous and stimulus-evoked pain including hyperalgesia and allodynia. Magnesium (Mg) deficiency has been proposed as a factor in the pathogenesis of diabetes-related complications, including neuropathy. In the central nervous system, Mg is also a voltage-dependant blocker of the N -methyl-d-aspartate receptor channels involved in abnormal processing of sensory information. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 57 publications
6
49
0
3
Order By: Relevance
“…Mg could be effective in pain relief by exerting the antinociceptive effect46, inhibiting TNF-α47, and modulating hypesthesia and hyperalgesia4849, by blocking the NMDA receptor. The pain relief effect of Mg has been illustrated by several studies in many cases, such as postoperative sore throat50, tourniquet pain51, major non-laparoscopic gastrointestinal surgery52, diabetic neuropathic pain53, cardiac surgery54, and cancer-related neuropathic pain55. The present study also demonstrated that the single-dose IA Mg was effective in pain relief after arthroscopic surgery.…”
Section: Discussionsupporting
confidence: 70%
“…Mg could be effective in pain relief by exerting the antinociceptive effect46, inhibiting TNF-α47, and modulating hypesthesia and hyperalgesia4849, by blocking the NMDA receptor. The pain relief effect of Mg has been illustrated by several studies in many cases, such as postoperative sore throat50, tourniquet pain51, major non-laparoscopic gastrointestinal surgery52, diabetic neuropathic pain53, cardiac surgery54, and cancer-related neuropathic pain55. The present study also demonstrated that the single-dose IA Mg was effective in pain relief after arthroscopic surgery.…”
Section: Discussionsupporting
confidence: 70%
“…Several lines of evidence indicate that magnesium enhances the analgesic effects of opioids, general, and local anesthetics in different animal models of pain (Assi, 2001;Liu et al, 2001;Nechifor, 2011). As a sole drug, magnesium demonstrated analgesic efficacy against neuropathic pain (Begon et al, 2000;Rondón et al, 2010). There are controversial results in the previous studies investigating the effect of magnesium in a model of somatic inflammatory pain induced by injection of formalin into the rat paw (Begon et al, 2002;Takano et al, 2000).…”
Section: Introductionmentioning
confidence: 81%
“…Neurokinin release from central terminals is controlled by numerous presynaptic modulatory receptors, including inhibition by GABA B (Marvizón et al, 1999; Riley et al, 2001; Zhang et al, 2010), α 2 -adrenergic (Takano et al, 1993) and opioid (Kondo et al, 2005; Beaudry et al, 2011; Chen et al, 2014) receptors, and facilitation by capsaicin (Marvizón et al, 2003), serotonin (Inoue et al, 1997) and NMDA (Liu et al, 1997; Trafton and Basbaum, 2000) receptors. In the condition of DNP, the overexpression of NMDA receptors (Tomiyama et al, 2005; Rondon et al, 2010) and decreased function of GABA B (Wang et al, 2007) at the primary afferent terminals mobilizes excessive SP release (Marvizón et al, 1999) and counteracts the effects of EM2. In the present study, we provided evidence that the decreased level of presynaptic MORs might account for the reduced efficacy of EM2 on SP release.…”
Section: Discussionmentioning
confidence: 99%